Blue Accounting and Sustainability: Assessing Long-Term Effects Beyond Profitability - Yohana Febiani Angi; Maria Immaculata Bahantwelu; Rr Lilis Intan Permatasari; Melianus E Tkela (Daengku: Journal of Humanities and Social Sciences Innovation, 2026)
This study aims to analyze the implementation of Blue Accounting in the seaweed industry through the valuation of ecosystem and biodiversity components and the development of an Environmental Profit and Loss (EP&L) framework. This study employed a quantitative approach using the Choice Experiment (CE) method to identify seaweed farmers’ preferences regarding sustainability attributes in the industry. Data were analyzed using the Multinomial Logit (MNL) model to estimate the influence of each attribute on respondents’ choices. Subsequently, Marginal Willingness to Pay (MWTP) was calculated to determine the economic value of environmental attributes. The MWTP estimates were then used to construct a Cost-Weighted Score Matrix and integrated into the Environmental Profit and Loss (EP&L) framework. The results indicate that coastal ecosystem conditions and the reduction of ice-ice disease incidence are the most influential attributes affecting respondents’ preferences. The highest MWTP value was associated with coastal ecosystem conditions, reflecting the strong willingness of local communities to support environmental improvement programs. The Cost-Weighted Score Matrix identified coastal ecosystem quality and disease control as the highest-priority factors for Blue Accounting implementation. Furthermore, the EP&L analysis demonstrated that incorporating environmental costs and ecosystem service values provides a more comprehensive assessment of business performance compared to conventional accounting approaches. Blue Accounting integrate economic and environmental values into the management of the seaweed industry. The application of Choice Experiment, MWTP, Cost-Weighted Score Matrix, and Environmental Profit and Loss provides a more comprehensive basis for supporting transparent, accountable, and sustainable decision-making in the seaweed industry of Rote Ndao Regency.